2006
DOI: 10.1007/s00427-006-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced Robo2 isoforms in zebrafish and rat

Abstract: Robo2, a member of the robo gene family, functions as a repulsive axon guidance receptor as well as a regulator of cell migration and tissue morphogenesis in different taxa. In this study, a novel isoform of the zebrafish robo2 (robo2_tv2), which included an otherwise alternatively spliced exon (CAE), has been characterized. Robo2_tv2 is expressed differentially in most non-neuronal tissues of adult zebrafish whereas robo2_tv1 expression to a great extent is restricted to the brain and eye. In zebrafish, robo2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…For example, alternative splicing of Robo2 and 3 transcripts results in isoforms with distinct affinity for Slit binding and/or differences in intracellular signaling (Camurri et al, 2004;Yue et al, 2006). Tissue-specific alternative mRNA splicing appears to contribute to the spatial complexity of Robo2 and 3 expression (Challa et al, 2005;Dalkic et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alternative splicing of Robo2 and 3 transcripts results in isoforms with distinct affinity for Slit binding and/or differences in intracellular signaling (Camurri et al, 2004;Yue et al, 2006). Tissue-specific alternative mRNA splicing appears to contribute to the spatial complexity of Robo2 and 3 expression (Challa et al, 2005;Dalkic et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…For example, alternative splicing of Robo2 and 3 transcripts results in isoforms with distinct affinity for Slit binding and/or differences in intracellular signaling (Camurri et al, 2004;Yue et al, 2006). Tissue-specific alternative mRNA splicing appears to contribute to the spatial complexity of Robo2 and 3 expression (Challa et al, 2005;Dalkic et al, 2006).Robo1 presents a different case, with alternative transcription start sites providing the potential to be independently regulated. A human Robo homolog was independently cloned from breast and small cell lung cancer cell lines as a potential tumor suppressor gene and designated as Dutt1 (Deleted in U-twenty twenty) (Sundaresan et al, 1998).…”
mentioning
confidence: 99%
“…Our work suggests that adherens junctions may act downstream of Slit-Robo signaling in HSCs. In addition, since Slit-Robo signaling has roles in gonad development in flies and in the mammalian ovary [65], and high throughput expression studies suggest that this signaling pathway is active in the mammalian testis, [66][68] it may function there as well. Data we present in the Drosophila testis represent the first mechanistic example of Slit-Robo signaling functioning in an intact adult stem cell niche.…”
Section: Discussionmentioning
confidence: 99%
“…Such a positive, axon growth-promoting function of Slit has previously been reported for various types of sensory neurons in mouse (Wang et al, 1999) and zebrafish (Yeo et al, 2004). While there are no detectable differences in robo2 mRNA expression across the population of RGCs (Lee et al, 2001), the zebrafish robo2 transcript has been shown to be alternatively spliced, giving rise to several isoforms, some of which are present only in certain tissues or developmental stages (Dalkic et al, 2006). In mouse spinal cord, two functionally antagonistic isoforms of Robo3 are present in the commissural neurons (Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%